Budaya Sosial Merokok Masyarakat Terhadap Status Kesehatan Jaringan Periodontal - Rosdiana, Rosdiana; Djunaedi, Djunaedi; Aditia, Donny (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Smoking is one of the factors that easily attaches debris to the teeth. This can increase the occurrence of bad mouth success, moreover the frequency of smoking in Indonesia is still high. From the results, it was found that smoking habits in men aged 14 years and over amounted to 45.8% and in women of the same age 2.9%. Bearing in mind that if debris is left unchecked it will develop into tartar and cause periodontitis which is a continuation of Gigivitis or gum pain. These disorders can be in the form of excessive plaque, caries on the crown and roots of the teeth, halitosis, tooth discoloration and others. Research objectives to determine and explain the influence of smoking habits and the condition of the periodontal tissue in the community. This research uses a descriptive type of research through an observational approach by researching and directly examining the state of dental and oral health in the community. The results of the study can be concluded that smoking habits with the incidence of periodontitis in adult males aged 36-45 years in Makassar with a total sample of 42 people are as follows: The incidence of periodontitis in adult male smokers aged 36-45 years in Makassar was found in the mild category of 59.5%. The incidence of periodontitis was based on smoking duration, where most of the study subjects experienced mild periodontitis with a smoking duration of 1-10 years by 26.2%.